Synthesis of Ag-doped ZnO nanoparticles for the photocatalytic degradation of phenol and dyes - Imboon Tanawat; Somyanonthanakun Wuttichai; Photiwut Pisanu; Khumphon Jeerawan; Ghosh Sougata; Tanna Ashish R.; Sridawong Laksanaphon; Chotikaprakhan Sutharat; Thongmee Sirikanjana (E3S Web of Conferences)
The morphological, optoelectronic, and dye degrading properties of Ag doped ZnONPs are reported herein which were fabricated using different concentrations of Ag and a hydrothermal method. The size of ZnONPs ranged from 33 to 45 nm. UV-Visible spectroscopy revealed a red- shift of the absorbance spectra confirming band gap reduction after Ag doping. The four luminescence peaks for the ZnONPs included a blue luminescence peak between 440 and 470 nm, a green luminescence peak between 470 and 570, a yellow luminescence peak between 570 and 585 nm, and a red luminescence peak between 585 and 780 nm. Superior photocatalytic dye degradation was noted where the 5% Ag-doped ZnONPs exhibited 99.12 % photocatalytic phenol degradation after 24 h with a rate constant equivalent to 0.2099 k (min-1) while the rate constants of 2.5922 and 2.3392 k (min-1) for the degradation of Rhodamine B and methylene blue dyes, respectively. Hence, the present Ag-doped ZnONPs should be further studied for diverse photocatalytic applications.